Korelasi kadar leptin serum terhadap derajat penyakit dermatitis atopik - Gde Ngurah Arya Ariwangsa; Made Wardhana; Luh Made Mas Rusyati (DiscoverSys Inc., 2019)
Background: Atopic dermatitis (AD) is a chronic and residual skin inflammatory disease in which the symptoms include intense itching, chronic exacerbations and remissions, with multifactorial etiologies. The role of leptin in DA is closely related to polarization of T cells towards Th1 cells resulting in the release of pro-inflammatory cytokines.Methods: A cross-sectional study was conducted among 30 atopic dermatitis patients at Sanglah General Hospital in the period of July-August 2018. The leptin examination was carried out using the ELISA method. Data analysis were performed using SPSS version 25.0 software with the Spearman correlation test to determine the relationship between levels of serum leptin and the severity of atopic dermatitis based on SCORAD.Results: Most of the respondents were females (66.7%) with an average leptin level was 25.75 + 18.21 pg/dL. The results showed a significant negative correlation between the level of serum leptin and the severity of DA (SCORAD) (r: -0.127; p: 0.043). However, there was a significant positive correlation between pH of the skin and SCORAD (r: 0.810 and p: <0.001).Conclusions: There is a negative correlation between level of serum leptin and SCORAD but it has a strong positive correlation between the pH of the skin and SCORAD.